Widows and inheritance violation: case studies of Zengeza 1 and 5 Chitungwiza 1997-2018 - Matamba, Memory (Midlands State University, 2019)
The dissertation is mainly focused on the widows continued experiences of property inheritance violations in Zimbabwe particularly Zengeza 1 and 5 in Chitungwiza. The cause and reasons why widows are still being disinherited their property rights after legal laws were implemented to protect them. Widows before the Administration of Estates Amendment Act of 1997 they faced violations towards their right to property inheritance. The first born usually the son or a male relative was the heir to the inheritance of the deceased and the heir was supposed to follow the needs of the widow but if was found out that this was not happening. Widows were being left without houses and their benefits were used to cater for the needs of the heir only. In 1997 the Administration of Estates Chapter 6 was amended to Administration of Estates Amendment Act which made the surviving spouse and children the beneficiaries of the inheritance. Zimbabwe had a dual legal system which has the general law and customary law that are used to govern and it was inherited from the colonial times. Reports by academic researchers and newspaper reports shows that widows are still being violated their rights. Interviews were used to gather information from the widows and other residents and the legal interns of Women and Law in Southern Africa. Secondary sources were also used such as journals, articles, newspapers and books. Violations that widows are facing are also as a result of the interpretation of the laws and they are being disinherited their rights. The violations are caused ignorance fear to ruin their relations with the in-laws, the interpretation of the laws and family traditions.